Wrocławska „Dzielnica” Wzajemnego Szacunku Czterech „Wyznań”. Idea, nazwa, działalność – kontekst ekumeniczny - Anna Sanecka (Język. Religia. Tożsamość, 2021)
The Wroclaw Quarter of Mutual Respect of the Four Denominations is a unique place not only on the map of Poland, but also of Europe. It is a place of long-term cooperation between representatives of two religions – Judaism and Christianity and three Christian denominations: Catholicism, Protestantism and Orthodoxy. For more than 20 years, the Quarter has been actively operating in the area of education and culture. The Quarter of Mutual Respect is a place of meetings, friendly cooperation and dialogue, which allows conducting truly ecumenical activities. The article presents these activities of the Quarter and the ideas that guided its creation and existence. It also points out certain linguistic issues concerning the name of the Quarter.